Minority Embeddedness and Economic Integration: Is Diversity or Homogeneity Associated with Better Employment Outcomes? - Demireva, Neli (2017)
Using data from the Managing Cultural Diversity Survey 2010 and the Ethnic Minority British Election Study 2010, we explore the activity and employment outcomes of majority and minority individuals in the UK, and examine their association with a variety of ethnic embeddedness measures. We do not find that white British respondents living in areas of high deprivation and diversity experience lower levels of economic activity or bad jobs. Deprivation rather than minority embeddedness stands out as the factor that serves to compound both majority and minority disadvantage. In the case of minorities, embeddedness does have some negative effects, although these are greatly attenuated once one takes into account the level of area deprivation.